Недопущення посягань на особисту безпеку засуджених у контексті реформування Державної кримінально-виконавчої служби України - Журавська, З.; Zhuravska, Z. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Розглянуто сучасний стан наукової розробки проблем забезпечення безпеки в установах виконання кримінальних покарань. Проаналізовано законопроекти, що мають безпосереднє відношення до забезпечення особистої безпеки засуджених. Зазначені вимоги і правила побудови правових норм, яких потрібно дотримуватись при видозміні чинного кримінально-виконавчого законодавства України. Автор дійшов висновку, що держава на правовому рівні вимушена створювати такі умови відбування покарання, які б забезпечували суспільну безпеку для всіх оточуючих, включаючи засуджених осіб. The article deals with the current state of scientific substantiation of problems dealing with security inthe places of detention where the convicts serve their sentence. The analysis is focused on the legal actsand bills of law related to the personal security of convicts and the need for modification of the existing penallaws in Ukraine. The author proposes a set of measures to be taken to improve the existing legal framework ofdraft laws and a variety of other legal sources aimed at the solution of the problem. It is concluded that the state at a legal level ought to create such conditions of serving the sentence, which could provide social security for all the others, including prisoners. Theauthor singles out penitentiary phenomena and processes occurring in the course of serving a sentence of imprisonment, which fall into a category of a constraining factor for prisoners and for the whole population.
Preventing Encroachments on Personal Security of Prisoners in the Context of Reforming the State Penal Service of Ukraine
Keywords: виконання кримінальних покарань; установи виконання покарань; Державна кримінально-виконавча служба; безпека; засуджений; execution of criminal penalties; penitentiary institutions State Penal Service; security; convicted